2013
DOI: 10.1007/s10439-013-0890-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved Accuracy with 3D Planning and Patient-Specific Instruments During Simulated Pelvic Bone Tumor Surgery

Abstract: In orthopaedic surgery, resection of pelvic bone tumors can be inaccurate due to complex geometry, limited visibility and restricted working space of the pelvis. The present study investigated accuracy of patient-specific instrumentation (PSI) for bone-cutting during simulated tumor surgery within the pelvis. A synthetic pelvic bone model was imaged using a CT-scanner. The set of images was reconstructed in 3D and resection of a simulated periacetabular tumor was defined with four target planes (ischium, pubis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 29 publications
6
104
1
Order By: Relevance
“…It concurred with the results in a simulated sawbone study that the 3D planning and PSI could improve the accuracy of pelvic bone tumor surgery. [14] Our finding suggested that the tumor PSI might even support a more difficult multiplanar osteotomy in the pelvic region with complex anatomy. This enabled surgeons to resect bone tumors with just adequate margin but yet it could maximally preserve the surrounding normal bone for reconstruction with a better function.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It concurred with the results in a simulated sawbone study that the 3D planning and PSI could improve the accuracy of pelvic bone tumor surgery. [14] Our finding suggested that the tumor PSI might even support a more difficult multiplanar osteotomy in the pelvic region with complex anatomy. This enabled surgeons to resect bone tumors with just adequate margin but yet it could maximally preserve the surrounding normal bone for reconstruction with a better function.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast to computer navigation assisted surgery, the tumor PSI could achieve an acceptable resection accuracy by a shorter time and did not involve bulky instruments and other supporting facilities. [14,15] Also, the favorable final Figure 5. (A) The design of PSI had the cutting platforms or slits that matched the planned resection planes; the flanges with the contoured shape that allowed a unique PSI positioning on the surgical accessible bone surface decided by the surgeons at the CAD software; and the K-wire holes on the flanges for stabilizing the PSI to the bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16]18 These studies document the unique ability 3D printing technology has to improve complex reconstructive procedures. In contrast, we directed our efforts toward the design and production of frequently utilized disposable medical equipment.…”
Section: Discussionmentioning
confidence: 98%
“…Personalized medicine means "providing the right treatment to the right patient at the right time" [4], one perspective of this approach being focused on designing, manufacturing and using customized instruments (such as surgical guides [3]) or implants [2] based on patient anatomical data.…”
Section: Introductionmentioning
confidence: 99%